PROTECTIVE EFFECTS OF SEA GRAPE SIMPLICIA ON LUNG HISTOPATHOLOGY IN PARACETAMOL-INDUCED RATS - Reyna Tasya Dhewanty; I Ketut Berata; Tri Komala Sari; Samsuri; I Made Merdana (Buletin Veteriner Udayana, 2025)
Caulerpa lentillifera, commonly known as sea grapes, is a green alga found in shallow sandy areas and around coral reefs. It contains chlorophyll A and B, polyphenols, flavonoids, tannins, and vitamins A, B1, B2, B6, B12, and C—all of which possess antioxidant properties. Antioxidants play a critical role in preventing and repairing cellular damage. This study aimed to evaluate the protective effects of C. lentillifera simplicia on the lung histopathology of white rats (Rattus norvegicus) induced with paracetamol. Twenty-five male rats were randomly assigned to five groups and treated over a 14-day period. Lung tissues were collected on day 15 for histopathological analysis, focusing on indicators such as hemorrhage, inflammation, congestion, and necrosis. Data were analyzed using the Kruskal–Wallis and Mann–Whitney tests. Paracetamol administration caused significant histopathological damage to lung tissues. However, rats treated with C. lentillifera simplicia exhibited notable improvements, with reduced severity of hemorrhage, inflammation, congestion, and necrosis compared to the paracetamol-only group. These findings indicate that C. lentillifera simplicia has a protective effect against paracetamol-induced lung injury, supporting its potential use as a natural antioxidant for lung tissue protection.